Enhancing Students’ Engagement and Speaking Skills through Interactive Activities in English Language Teaching: Teachers’ and Students’ Perspectives - Honey Jean Saura; Pit Dhale Capao; Liera Campos; Shelou Marie Bubuli; Joemar Miñoza; M. Saleh Yahya Himni (Asshika: Journal of English Language Teaching and Learning, 2025)
This literature review explores traditional and innovative English teaching activities that enhance students’ engagement and speaking skills. Thirty peer-reviewed studies published between 2020 and 2025 were analyzed thematically and chronologically. Traditional approaches such as role-playing, storytelling, language clubs, and group discussions, together with innovative practices like vlog creation, gamified learning, mobile-assisted learning, and TikTok-based tasks, have been found effective in improving fluency, confidence, and motivation. Both teachers and students expressed positive attitudes toward these activities. However, long-term implementation across diverse contexts remains underexplored. This review highlights the importance of blended pedagogical approaches and calls for future research into sustainable engagement-based English instruction.